Pembentukan Model Amalan Keusahawanan Sosial Islam dalam kalangan Usahawan Sosial Berjaya Muslim (Jurnal Pembangunan Sosial, 2018)
Islamic Social Entrepreneurship (ISE) is an activity that focuses on community social values based on the Islamic framework (akidah, syariah and moral) conducted by Sucessful Muslim Social Entrepreneurs (SMSE) to help the needy community. ISE is also one of the muamalat branches in improving the economy of a country. To implement ISE holistically, a model based on the Al-Quran and as-Sunnah should be developed to guide the SMSE groups involved with the vision and mission purpose. This paper is intended to analyze the ISE model which includes Islamic frameworks and Islamic values based on the Al-Quran and as-Sunnah. The research method used is content analysis based on past studies and referring to the Qur'an and as-Sunnah to obtain a detailed description of the ISE practice model. The findings show that the model of ISE practices among SMSE can be produced and thus can positively impact the social media perspective to improve the economy of the ummah and solve the social problems of society. Therefore, in-depth scientific discussion are highlighted in this study.